MOF(CuBDC)-Microcantilever IR Spectroscopy for Methane Sensing with High Sensitivity and Selectivity - Seungwan Seo; Seok Bin Kwon; Yangkyu Park (Chemosensors)
Methane, a greenhouse gas with 21 times the global warming potential of carbon dioxide, is increasingly subject to stringent emission regulations, driving the demand for high-performance methane sensors. This study proposes a novel IR spectroscopy technique based on a CuBDC-integrated microcantilever (CuBDC-microcantilever IR spectroscopy) for CH4 sensing, offering exceptional sensitivity and selectivity. The metal-organic framework (MOF) CuBDC was synthesized on the microcantilever using a drop-and-dry method facilitated by an intense pulsed light technique. Characterization via scanning electron microscopy, X-ray diffraction, and Fourier transform infrared spectroscopy confirmed the successful formation of CuBDC on the microcantilever. The CuBDC-microcantilever IR spectroscopy demonstrated a significantly enhanced sensitivity, with a differential amplitude at the CH4 characteristic peak approximately 13 times higher than that of a conventional Si microcantilever. Moreover, the limit of detection was determined to be as low as 14.05 ppm. The clear separation of the CH4 characteristic peak from the water and acetone vapor peaks also emphasized the sensor’s high selectivity. These findings highlight the superior sensitivity and selectivity of the proposed sensor, positioning it as a promising platform for CH4 detection in industrial and environmental applications.